Brand attachment in mediating of customer experience, hedonic value, and personalized experience on customer retention - Salma Fitri; Dean Salomo Anthonino Kumenaung (Jurnal STEI Ekonomi, 2025)
This study explores the influence of customer experience, hedonic value, and personalized experience on customer retention, with brand attachment as a mediating variable among skincare consumers. Amid the highly competitive skincare market in Indonesia, the research emphasizes the importance of cultivating meaningful experiences and personal connections to sustain loyalty. A survey-based quantitative approach and structural equation modeling were employed to test the hypothesized relationships. The findings reveal that customer experience, hedonic value, and personalized experience significantly enhance brand attachment, which in turn fosters stronger retention. These results highlight the pivotal role of emotional bonds in driving consumer loyalty. The study contributes to the marketing literature by integrating experiential and psychological factors into retention models. It offers practical insights for skincare firms to develop strategies that reinforce brand attachment and encourage long-term customer commitment.